Review of 54 patients with complete DiGeorge anomaly enrolled in protocols for thymus transplantation: outcome of 44 consecutive transplants - Markert, M. Louise; Devlin, Blythe H.; Alexieff, Marilyn J.; Li, Jie; McCarthy, Elizabeth A.; Gupton, Stephanie E.; Chinn, Ivan K.; Hale, Laura P.; Kepler, Thomas B.; He, Min; Sarzotti, Marcella; Skinner, Michael A.; et al. (Blood, 2007)
The purpose of this study was to characterize a large group of infants with complete DiGeorge anomaly and to evaluate the ability of thymus transplantation to reconstitute immune function in these infants. DiGeorge anomaly is characterized by varying defects of the heart, thymus, and parathyroid glands. Complete DiGeorge anomaly refers to the subgroup that is athymic (< 1%). The characteristics of 54 subjects at presentation and results from 44 consecutive thymus transplantations are reported. Remarkably, only 52% had 22q11 hemizygosity and only 57% had congenital heart disease requiring surgery. Thirty-one percent developed an atypical phenotype with rash and lymphadenopathy. To date, 33 of 44 subjects who received a transplant survive (75%) with post-transplantation follow-up as long as 13 years. All deaths occurred within 12 months of transplantation. All 25 subjects who were tested 1 year after transplantation had developed polyclonal T-cell repertoires and proliferative responses to mitogens. Adverse events developing after transplantation included hypothyroidism in 5 subjects and enteritis in 1 subject. In summary, diagnosis of complete DiGeorge anomaly is challenging because of the variability of presentation. Thymus transplantation was well tolerated and resulted in stable immunoreconstitution in these infants.